Factors Influencing Customer Loyalty toward Cosmetic Retail Stores in Surat Thani Province, Thailand - Chodchuang, Siripat; Hussanee , Wachiraya; Meenklan, Kasma; Plakpla, Thanatcha; Praditpon, Thansinee; Sani, Mareena; Chumee, Wijitra; Nunsai, Suwattana (Management Institute Faculty of Economics Universitas Andalas, 2025)
This research aims to study the factors related to perceived novelty of products and inspiration received that influence customer loyalty at retail stores in Surat Thani province. A questionnaire was used as a data collection tool, targeting 384 customers of the Klong Chan Jao store. The samples were selected using convenience sampling. The statistical methods used for data analysis included mean, standard deviation, and multiple regression analysis. The results showed that the customers' opinions in all aspects were rated the highest. In order from highest to lowest, these aspects were: customer loyalty (¯x= 4.34, S.D. = 0.60), perceived novelty of products (¯x= 4.27, S.D. = 0.58), and inspiration received (¯x = 4.25, S.D. = 0.59). The multiple linear regression analysis revealed that factors affecting customer loyalty at retail stores in Surat Thani province were statistically significant at the 0.05 level. The most significant factors, in order, were perceived novelty of products (β = 0.56, p = 0.05) and inspiration received (β = 0.32, p = 0.05) Entrepreneurs can increase customer loyalty by focusing on introducing innovative and trendy products that are in line with market trends, while inspiring customers through experiential marketing.